Drivers and barriers for Industry 4.0 readiness and practice: empirical evidence from small and medium-sized manufacturers. Issue 10 (27th July 2021) - Stentoft, Jan; Adsbøll Wickstrøm, Kent; Philipsen, Kristian; Haug, Anders
Abstract: The technological development e.g. in terms of Industry 4.0 is moving rapidly enabling manufacturing companies with new possibilities for digital transformations to offer products and services to current and new markets at competitive costs. A mixed-method approach is used to investigate the drivers and barriers for Industry 4.0 readiness and practice among Danish small and medium-sized manufacturers. Data is based on a questionnaire-survey among 190 manufacturers about their readiness for digitalized manufacturing and their actual practice in this area. A main finding is that it is the managers' lack of perceiving Industry 4.0 drivers, not their perceptions of high Industry 4.0 barriers that obstruct SMEs' development of Industry 4.0 readiness and their application of Industry 4.0 technologies. Using these insights provide four more nuanced interpretations of the significance of the Industry 4.0 challenges faced by the four case companies. The finding that SMEs seem to engage positively with Industry 4.0 barriers, when there is perceived a business case to do so, has important consequences for our understanding of the inertial dynamics surrounding SMEs' Industry 4.0 application, and consequently for guiding policy initiatives to promote Industry 4.0 adaptation among SMEs.